2016
DOI: 10.18632/oncotarget.14190
|View full text |Cite
|
Sign up to set email alerts
|

NFKB1-94insertion/deletion ATTG polymorphism and cancer risk: Evidence from 50 case-control studies

Abstract: Nuclear factor-kappa B1 (NF-κB1) is a pleiotropic transcription factor and key contributor to tumorigenesis in many types of cancer. Numerous studies have addressed the association of a functional insertion (I)/deletion (D) polymorphism (-94ins/delATTG, rs28362491) in the promoter region of NFKB1 gene with the risk of various types of cancer; however, their conclusions have been inconsistent. We therefore conducted a meta-analysis to reevaluate this association. PubMed, EMBASE, China National Knowledge infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 91 publications
3
41
0
1
Order By: Relevance
“…Polymorphisms rs696 and rs2910164 were in Hardy-Weinberg equilibrium in the control group (p=0.0967 and p=0.8020; respectively), while the rs28362491 variant was not (p=0.0001). The latter is in accordance with other European control groups which were not or were only approximately in equilibrium for the rs28362491 variant (19). Finally, the X-chromosome linked polymorphism rs3027898 was in Hardy-Weinberg equilibrium in the female control group, where the three genotypes existed (p=0.6615).…”
Section: Resultssupporting
confidence: 88%
“…Polymorphisms rs696 and rs2910164 were in Hardy-Weinberg equilibrium in the control group (p=0.0967 and p=0.8020; respectively), while the rs28362491 variant was not (p=0.0001). The latter is in accordance with other European control groups which were not or were only approximately in equilibrium for the rs28362491 variant (19). Finally, the X-chromosome linked polymorphism rs3027898 was in Hardy-Weinberg equilibrium in the female control group, where the three genotypes existed (p=0.6615).…”
Section: Resultssupporting
confidence: 88%
“…Polymorphism rs696 located in the 3’ UTR of NFKBIA gene was in Hardy‐Weinberg (HW) equilibrium in the control group ( P = 0.0637). The variant rs28362491 (‐94ATTG insertion/deletion) located in the promoter region of NFKB1 gene was not in HW equilibrium ( P = 0.0009), but this is in accordance with this reported for other European control groups . As far as concerned, the polymorphism rs3027898 located in the 3’ UTR of IRAK1 gene, which is mapped in X chromosome, was found in HW equilibrium in female control group where the three genotypes exist ( P = 0.4872).…”
Section: Resultssupporting
confidence: 85%
“…This association between NFKB1 gene and PV, where the insertion variant is the risk allele, is described for the first time in the literature. Previously, this polymorphism has been mainly associated with several cancer forms and heart diseases . In the present study, over‐presentation of the NFKB1 insertion allele was observed in PV patients as it was observed in the majority of studies referred to cancer …”
Section: Discussionsupporting
confidence: 61%
“…Referencing the previous studies [33,34], we carried out the trial sequential analysis (TSA) test for the assessment of conclusion robustness using the TSA viewer software (http://www.ctu.dk/tsa/) (type I error probability = 5%, statistical test power = 80%, and relative risk reduction = 20%).…”
Section: Trial Sequential Analysismentioning
confidence: 99%